Community Nursing Care of Chinese-Australian Cancer Patients: A Qualitative Study. Issue 4 (July 2015) - McKenzie, Heather; Kwok, Cannas; Tsang, Heidi; Moreau, Elizabeth
Abstract : Background: Providing quality care and support to cancer patients from minority cultures can challenge community nurses when language barriers and cultural complexities intersect with the need for complex care. Objectives: This article reports on a qualitative study that explores interactions between community nurses and Chinese-Australian cancer patients. Methods: The research method focused on particular nurse-patient encounters and involved preencounter and postencounter interviews with the nurse, postencounter interviews with the patient, and observation of the encounters. Participants included community nurses, Chinese cancer patients being cared for at home, and their carers if present. Results: Four themes were conceptualized: (1) the impact of language barriers on nurse-patient interactions, (2) patient understandings of the scope and objectives of healthcare services, (3) cultural complexities and sensitivities, and (4) valued care and support. The study demonstrates that, although many nurses do provide comprehensive, culturally competent care, language barriers can lead to task-oriented rather than comprehensive approaches, and other cultural complexities do have an impact on patient experiences and on the quality of nurse-patient interactions. Nevertheless, most patient participants experienced a feeling of security as a result of regular contact with a community nursing service. Conclusion: Cancer patients with complex care needs but limited English proficiency require support to negotiate complicated community services networks. Culturally competent community nurses can provide this support. Implications for Practice: The study highlights the need for continuing cultural competence education for community nurses and the importance of careful discharge planning to ensure continuity of care for this vulnerable patient group.